Characteristics of NSAIDs Prescription in Elderly Knee Osteoarthritis Patients - Wong, Janetta; Lumbuun, Nicolaski (Medicinus, 2022)
Introduction: The prescribing of non-steroidal anti-inflammatory drugs (NSAIDs) as pharmacological therapy for OA was found to be imprecise. In 2018, the rationality of NSAIDs prescribed at Wolter Monginsidi Hospital, Manado showed as much as 100% proper indication, 77% proper dose, and 89% proper medication. This shows that the rationality of NSAIDs prescription is still irrational. Irrational prescribing has the potential to result in side effects or the incidence of drug-related problemsAim: To determine the characteristics and the rationality of NSAIDs prescriptions in elderly knee OA.Methods: This is a descriptive study of 108 medical records for the period January 2020-April 2021 at BS Clinic, Semarang, using purposive sampling method.Result: Results showed the characteristics of elderly knee OA patients at BS Clinic were 74.1% women, 47.2% belonging to obese group, and 41.7% experiencing severe pain. Patient’s age had a median value of 66 years. In the number of comorbidity, the median value was 1. The rationality of NSAIDs prescription was 95,4% proper diagnosis, 100% proper drug, 97.2% proper dose, and 99.1% proper indication with the incidence of side effects of NSAIDs prescribing was 1.9%.